Heart failure : a case-based approach - Rahko, Peter S. (Demos Medical Publishing, LLC, 2014)
Heart failure is defined as the weakening of the heart's pumping power, and that it is unable to adequately supply the body with oxygen and nutrients. As the heart weakens it tends to stretch and stiffen under the stress. The kidneys respond by causing the body to retain fluid. If fluid builds up in the arms, legs, ankles, feet, lungs, or other organs, the body becomes congested, and congestive heart failure is the term used to describe the condition. Heart failure is the result of heart damage that can be caused by a number of diseases, including coronary artery disease, cardiomyopathy, atria.